Long-Term Follow-Up of UCLP Patients: Surgical and Orthodontic Burden of Care during Growth and Final Orthognathic Surgery Need. (November 2015) - Meazzini, Maria Costanza; Capello, Alice Varacca; Ventrini, Francesca; Autelitano, Luca; Morabito, Alberto; Garattini, Giovanna; Brusati, Roberto
Objective: The goal of this study was to evaluate the craniofacial morphology at 5 and 10 years of age and at the completion of growth, the need for final orthognathic surgery, and the orthodontic burden in a sample of patients with unilateral cleft lip and palate consecutively treated by the same surgeon with the same two-step protocol. Design: A sample of 62 adult patients with unilateral cleft lip and palate was retrospectively collected (mean age, 17.5 years). Lateral cephalograms at three time points were traced. The need for orthognathic surgery was assessed, subdividing the sample into an orthognathic surgery group and nonorthognathic surgery group. Time and modality of orthodontic treatment were recorded. Results: Cephalometric values related to maxillary growth (SNA, SNAns) and maxillomandibular relation (ANB, NAPg) were significantly different between the two groups already at 5 and 10 years of age. All patients presenting an ANB smaller than 2° at 5 years needed a Le Fort I osteotomy. Mandibular protrusion (SNB, SNPg) was not different at 5 and 10 years, but was different at the completion of growth. Patients with the same initial maxillomandibular relation did not show better growth when subjected to earlier or longer orthodontic treatment. Conclusion: Patients needing final jaw surgery had a more severe skeletal discrepancy during early childhood. The ANB angle at 5 years allowed doctors to identify 45% of the need for orthognathic surgery. The final craniofacial pattern does not seem to change significantly with early or prolonged orthodontic treatment.